Lifestyle of rural children and youth with overweight and obesity - Sygit, Katarzyna (Polish Journal of Public Health, 2010)
Introduction. Life style is responsible in 60% for a person’s health status. Numerous research articles on this problem indicate that the unhealthy lifestyle prevails over the health-promoting one in the environment of children and school youth from both towns/cities and villages.Aim. The aim of the study was to examine the life style of rural children and youth with overweight and obesity.Material and methods. The research covered 300 young people aged between 15 and 19 from a rural environment in the West Pomerania province. A questionnaire developed by the authors was used in the study and BMI index was applied to evaluate overweight and obesity. Surveying the rural youth lifestyle, the following factors were analysed: rational eating, stimulant consumption, leisure, stress, salt consumption, and physical activity.Results. Overweight occurs more frequently in the group of surveyed girls than boys. However, obesity occurred twice as frequently in the group of boys than in that of girls. There were 64.9% of the overweight respondents and as many as 78.3% of the obese ones who ate improperly while only 21.7% ate correctly. In the group of people with overweight, passive leisure prevailed (83.8%) over active leisure (16.2%), and in the group of people with obesity, passive leisure (86.9%) prevailed over the active one. In the group of people with overweight, 81.8% were averagely active and 8.1% - highly active. In the group of people with obesity, the respondents who were not active at all made up the largest group (52.2%). In the group with overweight as many as 21.0% of the respondents smoked, 48.6% drank alcohol and 43.2% used drugs. In the group of the obese respondents - 86.9% smoked, 43.5% drank alcohol and 30.4% used drugs.Conclusions. A significant part of the respondents with overweight and obesity were nourished incorrectly. The respondents mostly preferred passive resting. It was found that the group with obesity frequently experienced stress situations. No physical activity prevailed in the group of the overweight respondents. The overweight respondents and those with obesity systematically consumed stimulants.